Engaging the curriculum in higher education - Barnett, Ronald, 1947- (Society for Research into Higher Education., 2005)
There is greater interest than ever before in higher education: more money is being spent on it, more students are registered and more courses are being taught. And yet the matter that is arguably at the heart of higher education, the curriculum, is noticeable for its absence in public debate and in the literature on higher education. This book begins to redress the balance. Even though the term `curriculumÂ¿ may be missing from debates on higher education, curricula are changing rapidly and in s.